2018
DOI: 10.1080/14767058.2018.1487394
|View full text |Cite
|
Sign up to set email alerts
|

Early versus delayed removal of indwelling catheters in patients after elective cesarean section: a prospective randomized trial

Abstract: Early removal of urinary catheters after elective cesarean section is associated with reduced mobilization time and hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
2
14
1
1
Order By: Relevance
“…Randomized controlled trials suggested that a removal time of the urinary catheter at ≤6 h postoperatively seems to be more beneficial than immediate or >6 h removal for patients undergoing gynecologic surgeries, decreasing both the ambulation time and hospital stay [73,74]. In fact, many clinical trials recommended the removal of urinary catheters within the first postoperative day (within a period ranging from 3 to 24 h) for many surgical interventions that do not require long catheterization periods, such as pelvic rectal or colorectal resection surgery, gynecological procedures (gynecological laparotomy, cesarean section, colposuspension, vaginal plastic surgery, vaginal prolapse surgery, and vaginal, laparoscopic or abdominal hysterectomy) or urological surgeries (transurethral resection of the prostate) [74][75][76][77][78][79][80][81][82][83]. For operative patients who have an indication for an indwelling catheter, the removal of the catheter should be done as soon as possible postoperatively, preferably within 24 h [84].…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials suggested that a removal time of the urinary catheter at ≤6 h postoperatively seems to be more beneficial than immediate or >6 h removal for patients undergoing gynecologic surgeries, decreasing both the ambulation time and hospital stay [73,74]. In fact, many clinical trials recommended the removal of urinary catheters within the first postoperative day (within a period ranging from 3 to 24 h) for many surgical interventions that do not require long catheterization periods, such as pelvic rectal or colorectal resection surgery, gynecological procedures (gynecological laparotomy, cesarean section, colposuspension, vaginal plastic surgery, vaginal prolapse surgery, and vaginal, laparoscopic or abdominal hysterectomy) or urological surgeries (transurethral resection of the prostate) [74][75][76][77][78][79][80][81][82][83]. For operative patients who have an indication for an indwelling catheter, the removal of the catheter should be done as soon as possible postoperatively, preferably within 24 h [84].…”
Section: Discussionmentioning
confidence: 99%
“…This urodynamic study may portend a better safety profile for the 8-h group; however, this has not been popularized clinically. 8 Interventions like non-urethral catheterization, 3 , 4 immediate removal, 7 2-h removal, 10 6-h removal, 11 , 12 and 24-h removal 1 , 7 after caesarean section are flawed with urine retention morbidity. Immediate or very early removal of urethral catheter may increase the risk of urine retention necessitating the need for recatheterization.…”
Section: Introductionmentioning
confidence: 99%
“…Immediate or very early removal of urethral catheter may increase the risk of urine retention necessitating the need for recatheterization. 4 , 10 , 12 There is currently no consensus on the specific time for removal of urinary catheter post caesarean section. 12 The more the duration of urethral catheter in the urinary bladder, the higher the significant bacteriuria rate and the less incidence of urinary retention following caesarean section under spinal anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations